Source-sink relations and kernel weight differences in maize temperate hybrids - Gambin, Brenda Laura (2006)
Maize (Zea mays L.) kernel weight (KW) response to changes in assimilate availability per kernel during grain filling suggests that plants establish an early kernel sink potential that place them to grow close to a saturating assimilate availability condition during late grain-filling, meaning source limitations are common only early in kernel development. As maize reproductive efficiency in kernel set is not constant across different plant growth rates (PGR) around flowering, we used PGR per kernel during this period as an indicator of source availability per kernel. We tested whether PGR per kernel during flowering or during the effective grain-filling period were correlated to genotypic and environmental differences in final KW. Plant growth rate during both periods, KW, kernel growth rate during the effective grain-filling period, total duration of grain filling and kernel number per plant were measured in 12 commercial genotypes differing in KW sown at two sites under full irrigation. As expected from the curvilinear response relating kernel number per plant and PGR around flowering, increased PGRs resulted in higher PGR per kernel around this period (r2 = 0.86; p < 0.001). Differences in final KW due to genotypes or environments were significantly explained by the PGR per kernel around flowering (r2 = 0.40; p < 0.001), and not by the PGR per kernel during the effective grain-filling period. Genotypes differed in kernel growth rate (p < 0.001) and grain-filling duration (p < 0.001). The former was well explained by PGR per kernel around flowering (r2 = 0.66; p < 0.001), but showed no relationship with the PGR per kernel during the effective grain-filling period. Grain-filling duration was partially explained (r2 = 0.27; p < 0.01) by the ratio between PGR per kernel during the effective grain-filling period and kernel growth rate, but differences in duration were negligible compared to those observed in the ratio (∼41% versus ∼130%, respectively). Together, these results support the importance of source availability per kernel during early grain filling on the determination of maize potential sink capacity and final KW. Early resource availability per kernel was accurately estimated as PGR per kernel around the period of kernel number determination, which helped explain genotypic and environmental differences in maize final KW as well as in kernel growth rate.